Determinants Of Financial Distress In Retail Companies Listed On The Indonesia Stock Exchange In 2016 - 2019 - Indah Rahayu, Vika; Efrina, Liona; Dhonal, Rama; Yulismi, Yulismi; Fathoni, Zakky (Jurnal Smart: Sosial Ekonomi Kerakyatan, 2023)
The aim of this research is to provide empirical evidence on the impact of leverage, profitabilitas, likuiditas, company size, institutional ownership, and managerial ownership on financial distress. This research used 20 retail companies listed in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2016 - 2019. Data were analyzed using multiple regression method. Based on the result of analysis concluded that leverage, profitabilitas, likuiditas, institutional ownership, and managerial ownership have effect on financial distress, while company size no have effect on financial distress.